Crypto Trading and Bitcoin Prices: Evidence from a New Database of Retail Adoption - Raphael Auer; Giulio Cornelli; Sebastian Doerr; Jon Frost; Leonardo Gambacorta (Center for Economic Studies and ifo Institute (CESifo), 2023)
Prices for cryptocurrencies have undergone multiple boom-bust cycles, together with ongoing entry by retail investors. To investigate the drivers of crypto adoption, we assemble a novel database (made available with this paper) on retail use of crypto exchange apps at daily frequency for 95 countries over 2015–22. We show that a rising Bitcoin price is followed by the entry of new users. About 40% of these new users are men under 35, commonly identified as the most "risk-seeking" segment of the population. We confirm these findings by exploiting two exogenous price shocks: the crackdown of Chinese authorities on crypto mining in mid-2021 and the social unrest in Kazakhstan in early 2022. Moreover, we find that when prices rise retail investors buy, while the largest holders sell – making a return at the smaller users' expense. Overall, back of the envelope calculations suggest that around three-quarters of users have lost money on their Bitcoin investments.
Keywords: E42; E51; E58; F31; G28; L50; O32; 330; Bitcoin; cryptocurrencies; cryptoassets; regulation; decentralised finance; DeFi; retail investment